APPLICATION OF TELECOMMUNICATIONS IN SUPPORT OF ACCESS TO GOVERNMENT INFORMATION - Coll, David C.; Strickland, Lloyd H. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF